2012
DOI: 10.1182/blood-2011-12-399113
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of P1-Runx1 in mouse basophil development

Abstract: IntroductionBasophils are the least prevalent of the granulocytes, generally representing less than 1% of leukocytes in the peripheral blood. Basophil studies have been hampered by the rarity of these cells and, until recently, the lack of tools such as basophil-deficient mice with which to assess their roles in vivo. However, recent studies have unveiled evidence for several previously unrecognized roles for basophils that are distinct from those of mast cells. [1][2][3][4][5][6][7][8][9][10][11] In addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 47 publications
2
77
1
Order By: Relevance
“…Functional assays revealed that the causal variant altered enhancer activity and resulted in decreased CEBPA expression, which therefore helps drive the lineage choice between basophils and mast cells. Whether this lineage choice happens at the BMCP or a different myeloid progenitor stage is currently not resolved, and because our GWAS study did not measure mast cells in nonhematopoietic tissues, our findings cannot directly address this issue (71,72). In the region of another master TF, GATA2, our study identified a basophil and eosinophil count-associated variant within a similar CMP-restricted enhancer associated with GATA2 expression.…”
Section: Discussionmentioning
confidence: 81%
“…Functional assays revealed that the causal variant altered enhancer activity and resulted in decreased CEBPA expression, which therefore helps drive the lineage choice between basophils and mast cells. Whether this lineage choice happens at the BMCP or a different myeloid progenitor stage is currently not resolved, and because our GWAS study did not measure mast cells in nonhematopoietic tissues, our findings cannot directly address this issue (71,72). In the region of another master TF, GATA2, our study identified a basophil and eosinophil count-associated variant within a similar CMP-restricted enhancer associated with GATA2 expression.…”
Section: Discussionmentioning
confidence: 81%
“…The present data may provide a clue to explain, in part, the fate of basophils by documenting that at least some basophils can mature to, or generate, mast cells. However, as indicated by the P1 Runx-1-deficient mice where mast cell numbers are normal but basophils are few (21), not all mast cells need to have basophil precursors. Indeed, the present data showed that many blast colony-forming cells can produce mast cells without accompanying basophils.…”
Section: Discussionmentioning
confidence: 99%
“…Basophils appear to have nonredundant functions in vivo (17)(18)(19), but common progenitor cells for basophils and mast cells have been described (20). However, in P1 runt-related transcription factor-1 (Runx1)-deficient mice, basophils are severely depleted, but mast cell numbers are normal (21). In the present experiments, the development of basophils from blast colony-forming cells was also monitored to clarify their relationship to mast cells.…”
mentioning
confidence: 90%
“…The ordered expression of two transcription factors, GATA-2 and C/EBPα, appears to regulate the commitment of progenitor cells into the basophil lineage (30,32). Of note, mice deficient in the distal promoter-derived Runt-related transcription factor 1 (P1-Runx1) show severe basophilopenia with no apparent anomaly of mast cell, neutrophils, or eosinophils (33), indicating the requirement of P1-Runx1 for the later stage of basophil development. Recent studies demonstrated that basophils express GATA-1 (30,32,34), but its functional significance remains to be determined.…”
Section: Significancementioning
confidence: 99%